2016
DOI: 10.1371/journal.pone.0158963
|View full text |Cite
|
Sign up to set email alerts
|

Ajwa Date (Phoenix dactylifera L.) Extract Inhibits Human Breast Adenocarcinoma (MCF7) Cells In Vitro by Inducing Apoptosis and Cell Cycle Arrest

Abstract: IntroductionPhoenix dactylifera L (Date palm) is a native plant of the Kingdom of Saudi Arabia (KSA) and other Middle Eastern countries. Ajwa date has been described in the traditional and alternative medicine to provide several health benefits including anticholesteremic, antioxidant, hepatoprotective and anticancer effects, but most remains to be scientifically validated. Herein, we evaluated the anticancer effects of the Methanolic Extract of Ajwa Date (MEAD) on human breast adenocarcinoma (MCF7) cells in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 41 publications
3
52
0
3
Order By: Relevance
“…This data suggests that ADPE treatment pushes the cancer cells into late apoptosis stage. A previous study has also reported that methanolic extract of Ajwa dates induces apoptosis in breast cancer MCF-7 cells by increasing the percentage of cells in late apoptosis [20]. DNA fragmentation data also confirmed the apoptosis-inducing efficacy of ADPE against MDA-MB-231 cells.…”
Section: Discussionsupporting
confidence: 67%
“…This data suggests that ADPE treatment pushes the cancer cells into late apoptosis stage. A previous study has also reported that methanolic extract of Ajwa dates induces apoptosis in breast cancer MCF-7 cells by increasing the percentage of cells in late apoptosis [20]. DNA fragmentation data also confirmed the apoptosis-inducing efficacy of ADPE against MDA-MB-231 cells.…”
Section: Discussionsupporting
confidence: 67%
“…However, the most attention-grabbing effects are highlighted for its activities against various kinds of cancers. Its anticancerous, antiproliferative, and antiangiogenic activities are reported against mammary cancer [11], colon cancer, [26] and breast cancers [27].…”
Section: Introductionmentioning
confidence: 99%
“…Natural or herbal medicines are often used as alternative forms of chemotherapy, due to low mortality and side effects (10). Currently, novel anticancer agents from natural products have become increasingly popular (11). In the history of Traditional Chinese Medicine (TCM), medicinal plants and their extracts have been used to treat various diseases.…”
Section: Introductionmentioning
confidence: 99%